• Dec 7th 2012, 07:27 PM
rikki397
I need help getting the variable b by itself
this is what i have so far but need help finishing it. If you could show step by step instructions that'd be great.
2ax=-b +/- sqrt(b^2-4ac)
+b +b
(2ax+b)^2= +/-sqrt( b^2-4ac)^2
(2ax+b)^2= b^2-4ac
• Dec 7th 2012, 11:01 PM
MarkFL
If you are trying to take the quadratic formula and solve for $\displaystyle b$, it will be far simpler to take the quadratic from which the formula is derived, and solve that for $\displaystyle b$:

$\displaystyle ax^2+bx+c=0$

$\displaystyle bx=-(ax^2+c)$

$\displaystyle b=-\frac{ax^2+c}{x}$
• Dec 8th 2012, 06:04 AM
rikki397
I know t would be easier to do it that way but the question asks to go from the formula i posted but thanks!
• Dec 8th 2012, 09:10 AM
MarkFL
Well, we can begin with the quadratic formula:

$\displaystyle x=\frac{-b\pm\sqrt{b^2-4ac}}{2a}$

$\displaystyle 2ax=-b\pm\sqrt{b^2-4ac}$

$\displaystyle 2ax+b=\pm\sqrt{b^2-4ac}$

$\displaystyle 4a^2x^2+4abx+b^2=b^2-4ac$

$\displaystyle 4a^2x^2+4abx+4ac=0$

With $\displaystyle a\ne0$ we have:

$\displaystyle ax^2+bx+c=0$